The protective effect of lisinopril on membrane-bound enzymes in myocardial preservation - (:unkn) unknown (WILEY, 2000)
A number of studies have reported that oxidant stress reduces the activity of isolated Na+ - K+ ATPase and Ca2+ ATPase which are known to affect the cell membrane integrity. The aim of the study is to determine whether the administration of lisinopril is able to protect the membrane-bound enzyme levels in isolated guinea pig hearts and also ascertain whether or not a relationship exists between oxygen free radicals and membrane bound Na+ - K+ ATPase and Ca2+ ATPase. Forty guinea pig hearts were studied in an isolated Krebs-Henseleit solution-perfused Langendorff cardiac model. In all groups cardioplegic: arrest was achieved by administering St. Thomas' Hospital cardioplegic solution (STHCS). Group 1 (control, n = 10) received only STHCS. Group 2 (n = 10) were arrested with lisinopril (1 mu mol 1(-1)) added STHCS, Group 3 (n = 10) were pretreated with oral lisinopril (0.2 mg kg(-1) twice a day) for 10 days and then arrested with STHCS. Group 4 were also pretreated with oral lisinopril (0.2 mg kg(-1) twice a day for 10 days), arrested with STHCS and reperfused with lisinopril added to Krebs-Henseleit solution (1 mu mol 1(-1)). Hearts were subjected to normothermic global ischaemia for 90 min and then reperfused at 37 degrees C. Pretreatment and addition of lisinopril in the reperfusion buffer improved the levels of membrane-bound enzymes. When the treated groups were compared with control hearts, the best results were achieved in group 4. The Na+ - K+ and Ca2+ ATPase levels increased from 466.38+/-5.99 to 560.12+/-18.02 and 884.69+/-9.13 to 1287.71+/-13.01 nmolPi mg(-1) protein h(-1) respectively (p < 0.05). These results suggest that lisinopril protects the cell membrane integrity and lessens free radical-induced oxidant stress. Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: cardioplegia; Ca2+ ATPase; Na+-K+ ATPase; lisinopril; ISCHEMIA-REPERFUSION INJURY; FREE-RADICALS; RAT-HEART; INHIBITORS; ENALAPRIL; TRANSPORT; REDUCTION; ATPASE; CA-2+